Kontribusi BUMN (Badan Usaha Milik Negara) Pada SektorEkonomi Dalam Menghadapi Pandemi Covid-19 - Falentino Theodoris Manasye Davids; Andhika Ahza Rachmadhani; Kanaya Adna Maharan; Ria Kasanah; Surya Raka; Dyah Permata Budi Asri (Wijayakusuma Law Review, 2021)
The objective of this research is to find out how the contribution of SOEs in the economic sector in the face of theCovid-19 pandemic which threatens economic stability and the consequences of the Covid-19 pandemic in theeconomic sector. The research method used was qualitative by following the typology of normative legalresearch. The research data were collected by means of literature and document studies. The data that has beencollected will be identified and arranged systematically and written descriptively and analyzed qualitatively. Theresearch results obtained are: 1. Contribution of SOEs in the economic sector in the context of facing the Covid-19pandemic, including a. The State Electricity Company (PLN) which contributes to providing free electricityassistance; b. PT Jamkrindo and PT Askrindo contributed in providing credit guarantees; c. Pegadaian, PNM, andBRI contributed in providing interest subsidy incentives. 2. The consequences arising from the Covid-19pandemic in the economic sector include household consumption or people's purchasing power of the economywhich has decreased drastically, there is prolonged uncertainty so that investment weakens and has implicationsfor the cessation of business, and the whole world is experiencing economic downturn so that Commodity pricesfell and Indonesian exports to several countries also stopped.